CdSe charge obtaining for single crystals growth in alkaline solutions - Sofronov, D.S.; Mormilo, P.V.; Kovalenko, N.O.; Sofronova, E.M.; Matejchenko, P.V.; Bryleva, E.Yu.; Kapustnik, A.K.; Terzin, I.S. (Functional Materials, 2018)
Cadmium selenide charge obtaining is proposed by interaction of cadmium nitrate with selenium in alkaline solution in the presence of hydrazine. It is shown that irrespective of alkali concentration and synthesis time, spherical particles (100-200 nm) of cadmium selenide with wurtzite structure are formed. Yield of the desired product increases with increasing the alkali concentration in the solution and the synthesis time and reaching a maximum of 97 wt. %. The grown crystal CdSe by the Bridgman method from the synthesized charge is optically transparent, does not contain large macrodefects and visible block boundaries.